2020
DOI: 10.1111/nmo.13809
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antegrade continence enema treatment and sacral nerve stimulation for children with severe functional constipation and fecal incontinence

Abstract: Background To compare antegrade continence enema (ACE) treatment and sacral nerve stimulation (SNS) in children with intractable functional constipation (FC) and fecal incontinence (FI). Methods We performed a retrospective review of children 6‐18 years old with FC and FI treated with either ACE or SNS at our institution. We recorded symptoms at baseline, 6 months, 12 months, 24 months, and their most recent visit after starting treatment. We compared improvement in FI, bowel movement (BM) frequency, abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…ACE has been evidenced to be useful in the management of NBD, which is characterized by chronic constipation and/or FI; ACE via cecostomy or MACE had similar continence outcomes ( 66 ). A retrospective review of 6–18-year-old children with FC and FI treated with either ACE or SNS showed that SNS was more effective against FI and ACE in improving the stool frequency and soothing abdominal pain ( 67 ). Another comparative study by Born et al reported that MACE might be more attractive than cecostomy tube in avoiding repeated procedures and radiation exposure ( 68 ).…”
Section: Management Of Fi In Children and Adolescentsmentioning
confidence: 99%
“…ACE has been evidenced to be useful in the management of NBD, which is characterized by chronic constipation and/or FI; ACE via cecostomy or MACE had similar continence outcomes ( 66 ). A retrospective review of 6–18-year-old children with FC and FI treated with either ACE or SNS showed that SNS was more effective against FI and ACE in improving the stool frequency and soothing abdominal pain ( 67 ). Another comparative study by Born et al reported that MACE might be more attractive than cecostomy tube in avoiding repeated procedures and radiation exposure ( 68 ).…”
Section: Management Of Fi In Children and Adolescentsmentioning
confidence: 99%
“…[ 47 ] A retrospective review of pediatric patients with functional constipation and functional incontinence who were treated with either ACE or SNS showed that although both ACE and SNS lead to improvement in both pediatric functional constipation and functional incontinence, SNS was more effective for functional incontinence and ACE was more effective for improving bowel movement frequency, abdominal pain, and laxative discontinuation. [ 48 ]…”
Section: Sacral Nerve Stimulationmentioning
confidence: 99%
“…ACE increased the number of bowel movements per week and decreased abdominal symptom, and SNS decrease episodes of FI after 2 years of treatment. 31 It is important to consider how longer term follow-up will be able to provide more information regarding the compliance of the patient, proposed duration of therapy, and the sustainability of a benefit of the neuromodulation while it is in use, and after it is discontinued. It also seems important to highlight that the majority of the published papers on the use of SNS therapy have been published by a single center.…”
Section: Ileostomymentioning
confidence: 99%
“…In the future, evaluation of other centers' experience, will make it easier to have a better understanding of the results and the outcomes of SNS. 28,31…”
Section: Ileostomymentioning
confidence: 99%